Wood wide web design. A computational model to adapt the cities design with mycorrhizal networks - Reategui, Jose L. (2022)
The design and construction of architectural objects and cities design seeks to relate to their environment through local data collection systems that understand the environment as a static system related with bio dynamics where trees represent a community with low interaction. It was demonstrated that almost all forests in the world are communities with trees in constant communication through mycorrhiza fungi, forming an essential part of the forest's livelihood, its resilience, and ability to adapt to human intervention events. This research proposes a computational model designed to incorporate vectors into a parametric design system with the aim of showing nutrient flows based in the link between trees and mycorrhiza fungi in project intervention areas and existing construction, connecting the cities design proposals and building and cities performance analysis with the objectives of contribute to conserving, protecting, and restoring life on earth in a post-carbon era from architecture, urban design, and landscaping. These vectors are the result of the analysis of orchid health and the use satellite images in different bands, all this process is supported by machine learning, Internet of Things, edge and cloud computing technologies.